2013
DOI: 10.3126/jmcjms.v1i1.7887
|View full text |Cite
|
Sign up to set email alerts
|

Alpha and Beta amylase activity of Fagopyrum esculentum (Buckwheat): A Medicinal Plant

Abstract: Background and Objectives: Fagopyrum esculentum, common buckwheat popularly known as mithe fapar is one of the staple food crops of the mountain region. Traditionally, it is used to treat constipation and bowel upsets. It is also used by diabetic in different parts of Nepal and India. Due to its high nutritive and medicinal value, medical scientist and researchers are interested in developing this as pharmaceutical plant. In this regard department of biochemistry, College of Applied Education and Health Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…All Rights Reserved. same study cited above(Prakash and Deshwal, 2013) it was found that the enzyme activity was retained at 60% in 2 M NaCl after 24 hour incubation, while full activity was found in 0.5 M NaCl for the same duration of incubation. Therefore, changes in salt concentrations could also be studied to check for longer activity retention.…”
supporting
confidence: 72%
“…All Rights Reserved. same study cited above(Prakash and Deshwal, 2013) it was found that the enzyme activity was retained at 60% in 2 M NaCl after 24 hour incubation, while full activity was found in 0.5 M NaCl for the same duration of incubation. Therefore, changes in salt concentrations could also be studied to check for longer activity retention.…”
supporting
confidence: 72%
“…after 1 hour (Prakash and Deshwal, 2013). Therefore, it is possible that incubation at lower temperature would have shown higher activity levels for a longer time in the present study.…”
Section: Resultsmentioning
confidence: 77%
“…Finger millet seeds germinated for 72 hours were found suitable for amylase activity in yet another study (Nirmal and Murali Krishna, 2003) β-amylase was found to be catalytically active in African finger millet seed malted for 96 hours (Kolawole, 2009). Other reports exist showing varying degree of germination time (3-5 days) for best amylase activity in different crops (Mawahib et al, 2010), (Nerkar et al, 2011), (Usha et al, 2011), (Prakash and Deshwal, 2013).…”
Section: Resultsmentioning
confidence: 96%
“…The earliest record of the medical function of TB in Chinese history traces back to about 2,000 years ago ( Lin, 1994 ). However it has only been in recent years that TB, a health-beneficial crop, has attracted a large attention for its nutraceutical functions ( Kreft, 2016 ; Prakash & Deshwal, 2013 ).…”
Section: Introductionmentioning
confidence: 99%